Decoding the role of platelets in tumour metastasis: enigmatic accomplices and intricate targets for anticancer treatments - Zhao, Jessie; Huang, Angela; Zeller, Johannes; Peter, Karlheinz; McFadyen, James D. (Frontiers in Immunology, 2023)
The canonical role of platelets as central players in cardiovascular disease by way of their fundamental role in mediating thrombosis and haemostasis is well appreciated. However, there is now a large body of experimental evidence demonstrating that platelets are also pivotal in various physiological and pathophysiological processes other than maintaining haemostasis. Foremost amongst these is the emerging data highlighting the key role of platelets in driving cancer growth, metastasis and modulating the tumour microenvironment. As such, there is significant interest in targeting platelets therapeutically for the treatment of cancer. Therefore, the purpose of this review is to provide an overview of how platelets contribute to the cancer landscape and why platelets present as valuable targets for the development of novel cancer diagnosis tools and therapeutics.